Unambiguous definition of ambiguous loss: Exploring conceptual boundaries of physical and psychological types through content analysis - Zasiekina, Larysa; Abraham, Andrea; Zasiekin, Serhii (East European Journal of Psycholinguistics, 2023)
The article aims to extend our understanding of physical and psychological types of ambiguous loss through a systematic review based on content and psycholinguistic analysis. The study encompassed articles aligned with ambiguous loss published between 2019-2023, retrieved from PsycINFO, Web of Science (WoS), and Scopus. To eliminate the bias in the literature review, the study extracted published articles, dissertations, book chapters, and preprints with titles containing the search term “ambiguous loss”. Two reviewers (the first and the third authors worked independently) examined titles and abstracts and identified papers highlighting physical (n=34) or psychological (n=23) types of ambiguous loss. The physical type results from physical absence of meaningful persons (e.g. abducted, missing, adopted), while the psychological type results from psychological absence of meaningful persons (e.g. dementia, mental illness, addiction). The study applies the conceptual and relational content analysis of Leximancer (version 4.5) to develop three cluster maps and lists of concepts separately for physical and psychological types and all selected papers published between 2019-2023. The results show that the physical type primarily encompasses situations related to adoption, potentially leading to the ambiguous loss experienced by both biological parents and children when facing forced separation. Psychological type includes parents of children with disabilities, shaken baby syndrome, and caregivers of individuals with brain injuries and cancer. The present study indicates that the conceptual boundaries between physical and psychological types of ambiguous loss are not only expanding but also erasing, giving way to new applications in settings such as the COVID-19 pandemic, organ donor families, and sexual and gender minority.Disclosure StatementNo potential conflict of interest was reported by the authors.Data Availability StatementThe data that support the findings of this study are openly available in Mendeley Data: Zasiekina, Larysa; Zasiekin, Serhii (2023), “Ambiguous loss_abstracts_2019-2023”, Mendeley Data, V1, https://doi.org/ 10.17632/dscy8m4g37.1* Corresponding author: Larysa Zasiekina, 0000-0001-8456-0774 zasyekina.larisa@vnu.edu.ua